DYNAMIC STIFFNESS OF HIGH SPEED CUTTING (HSC) LINEAR MOTOR MACHINE TOOL - Zoran PANDILOV (Editura Politehnica, 2024)
In this paper a model of the feed drive system with disturbance force for High Speed Cutting (HSC) linear motor machine tool tool is given. The dynamic stiffness for the proposed model is analysed. A simulation of the influence of some parameters on feed drive dynamic stiffness is performed with the simulation program MATLAB & SIMULINK. Correctness of the proposed model is verified with an experimental measurement of the dynamic stiffness of the feed drive on the prototype HSC linear motor machine tool (HSC 11)
Keywords: dynamic stiffness, feed drive, HSC linear motor machine tool